2018
DOI: 10.5336/cardiosci.2018-61921
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Whole Blood Viscosity and Deep Vein Thrombosis

Abstract: The forgotten variable of shear stress in mitral annular calcification: whole blood viscosity. Med

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Increased blood viscosity is a risk factor for deep vein thrombosis [3,39]. Blood flow is slow in veins; therefore, blood viscosity becomes relatively high (viscosity = shear stress/shear rate).…”
Section: Infection and Venous Thrombosismentioning
confidence: 99%
“…Increased blood viscosity is a risk factor for deep vein thrombosis [3,39]. Blood flow is slow in veins; therefore, blood viscosity becomes relatively high (viscosity = shear stress/shear rate).…”
Section: Infection and Venous Thrombosismentioning
confidence: 99%
“…[ 16 ] In another study, WBV was found to be related with susceptibility for deep vein thrombosis. [ 17 ] Along with the development of endothelial dysfunction, lipoproteins start to accumulate in subendothelial region and at the end of this inflammatory process atherom plaques occur. There are substantial data demonstrating the correlation between increased inflammatory gene expression and LSR.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of a massive increase in the relative mass of RBC is an increase in the viscosity of whole blood, primarily by increasing the number of particles per unit of blood volume and, therefore, increasing the peripheral resistance to blood flow [ 64 ]. Viscosity is defined as the ratio between the shearing effort and the shear rate and is a risk factor for deep venous thrombosis, creating a procoagulant state through thrombocytosis and increasing the concentration of the circulating tissue factor [ 65 ]. Mean corpuscular volume is considered to have qualitative effects on blood rheology, rather than quantitative effects, such as hematocrit [ 66 ].…”
Section: Discussionmentioning
confidence: 99%